Clock Gene Evolution: Seasonal Timing, Phylogenetic Signal, or Functional Constraint? - Krabbenhoft, Trevor J. (Oxford University Press, 2014)
Genetic determinants of seasonal reproduction are not fully understood but may be important predictors of organism responses to climate change. We used a comparative approach to study the evolution of seasonal timing within a fish community in a natural common garden setting. We tested the hypothesis that allelic length variation in the PolyQ domain of a circadian rhythm gene, Clock1a, corresponded to interspecific differences in seasonal reproductive timing across 5 native and 1 introduced cyprinid fishes (n = 425 individuals) that co-occur in the Rio Grande, NM, USA. Most common allele lengths were longer in native species that initiated reproduction earlier (Spearman’s r = −0.70, P = 0.23). Clock1a allele length exhibited strong phylogenetic signal and earlier spawners were evolutionarily derived. Aside from length variation in Clock1a, all other amino acids were identical across native species, suggesting functional constraint over evolutionary time. Interestingly, the endangered Rio Grande silvery minnow (Hybognathus amarus) exhibited less allelic variation in Clock1a and observed heterozygosity was 2- to 6-fold lower than the 5 other (nonimperiled) species. Reduced genetic variation in this functionally important gene may impede this species’ capacity to respond to ongoing environmental change.